Environmental Bond Degradation of Different Laminated Glass Panels - El-Sisi, Alaa; Elsawi Mahmoud, Mohamed; El-Emam, Hesham; Elbelbisi, Ahmed; Salim, Hani (Polymers, 2024)
Since buildings are designed to endure over time, it is crucial to comprehend how laminated glass (LG) windows, and consequently, the polymer interlayer materials, respond to weathering. This paper explores the impact of accelerated humidity on the mechanical properties of several polymer interlayer materials and LG sections. The study specifically focuses on three polymer interlayer materials of industrial interest: polyvinyl butyral (PVB), ethylene-vinyl acetate (EVA), and ionomer (SG). To examine the environmental effects, testing setups were devised to subject the polymeric materials and LG panels to specific conditions. Uniaxial tension coupons and LG disks were submerged in a water bath to simulate the environmental effect. A dedicated testing fixture was designed and manufactured for the LG disks. The results showed that the properties of EVA, including strength, maximum strain, and toughness, were not significantly affected by the environmental conditions. However, the properties of SG5000 were notably impacted, with a significant reduction in its bond strength due to water immersion.